Reasonable Accommodation Requirements under Workers' Compensation in Ontario - Gunderson, Morley; Hyatt, Douglas; Law, David (Relations industrielles / Industrial Relations, 1995)
A relatively new and potentially important administrative forum for interpreting the concept of reasonable accommodation has been created by the Ontario Workers' Compensation Act as amended in 1989. The reuised act contained provisions requiring employers to reemploy, and where necessary make reasonable accommodations for, workers following an injury. Though representing an important reformation for the workers' compensation system, accommodation requirements are present in other labour market policy initiatives. This paper discusses the accommodation requirements in other legislation and jurisprudence in Canada, describes the recent reforms to the Ontario Workers' Compensation Act in which accommodation represents an integral component, and outlines the new and emerging jurisprudence under the revised act.